Large-scale meta-analysis highlights the hypothalamic–pituitary–gonadal axis in the genetic regulation of menstrual cycle length. (7th September 2018) - Laisk, Triin; Kukuškina, Viktorija; Palmer, Duncan; Laber, Samantha; Chen, Chia-Yen; Ferreira, Teresa; Rahmioglu, Nilufer; Zondervan, Krina; Becker, Christian; Smoller, Jordan W; Lippincott, Margaret; Salumets, Andres; et al.
Abstract: The normal menstrual cycle requires a delicate interplay between the hypothalamus, pituitary and ovary. Therefore, its length is an important indicator of female reproductive health. Menstrual cycle length has been shown to be partially controlled by genetic factors, especially in the follicle-stimulating hormone beta-subunit ( FSHB ) locus. A genome-wide association study meta-analysis of menstrual cycle length in 44 871 women of European ancestry confirmed the previously observed association with the FSHB locus and identified four additional novel signals in, or near, the GNRH1, PGR, NR5A2 and INS-IGF2 genes. These findings not only confirm the role of the hypothalamic–pituitary–gonadal axis in the genetic regulation of menstrual cycle length but also highlight potential novel local regulatory mechanisms, such as those mediated by IGF2 .